Application of the 27Al NMR spectroscopy to studies of mechanisms of cyclic esters polymerization - Kowalski, A.; Florczak, M.; Libiszowski, J.; Majerska, K.; Duda, A. (Polimery, 2022)
On account of a vast use of the aluminum-containing initiators and catalysts for the polymer synthesis the applications of the 27Al NMR spectroscopy to studies of the polymerization mechanisms is described. In the extensive introduction the specific features of Al atom, important with regard to the 27Al NMR spectroscopy, are discussed. The latter include strong tendency of the organoaluminum compounds to aggregation and quadrupolar character of the 27Al nucleus. Attention is also drawn to some pitfalls in the quantitative analysis of the 27Al NMR spectra which result from an extraneous multinuclear probe head signal, base-line rolling, and the absorption bands broadening at lower temperatures. Finally, examples of application of the 27Al NMR to determining the active centers structure in the ring-opening polymerization of ?-caprolactone (CL) and L,L-lactide (LA) initiated with dialkylaluminum alkoxides, aluminum tris-alkoxides or dialkylaluminum alkoxide/(S)-(+)-2,2’-[1,1’-binaphtyl-2,2’-diylbis-(nitrylmethilidyne)diphenol] [SB(OH)2] system are reported in more detail.